Weighted Orlicz regularity estimates for fully nonlinear elliptic equations with asymptotic convexity - Mikyoung Lee (World Scientific Publishing Co. Pte Ltd, 2022)
We prove interior Hessian estimates in the setting of weighted Orlicz spaces for viscosity solutions of fully nonlinear, uniformly elliptic equations F(D2u,x)=f(x)in B1 under asymptotic assumptions on the nonlinear operator F. The results are further extended to fully nonlinear, asymptotically elliptic equations.